Dysfunctional Voiding and Incontinence Scoring System for Children and Adolescents: A Tool to Predict Clinical Course and Outcome - Sommer-Joergensen, Vivienne; Sarcevic, Jelena; Haecker, Frank-Martin; Holland-Cunz, Stefan; Gros, Stephanie J.; Frech-Dörfler, Martina (European Journal of Pediatric Surgery, 2022)
Introduction Lower urinary tract symptoms (LUTS) in children are common. In 2005, Akbal et al published the dysfunctional voiding and incontinence scoring system (DVAISS) to assess patient's symptoms. Our study aimed to determine the value of this scoring system for predicting the severity and clinical course of voiding abnormalities in children and adolescents.Material and Methods Patients' symptoms were scored using the DVAISS in children and adolescents with LUTS presenting for the first time to our pediatric urology department between January 2010 and December 2015. We correlated the calculated score with voiding volume, clinical course, and outcome.Results A total of 168 patients (113 boys, 55 girls; age 5–18 years) with isolated LUTS were included. In 53 patients (group 1), the DVAISS score was less than or equal to 8.5 and in the other 115 patients (group 2), the score was greater than 8.5 suggestive for relevant voiding abnormalities. Patients in group 1 showed a significantly higher average voiding volume (200 vs. 110 mL, p = 0.001). The median time for symptom resolution was significantly higher in group 2 than group 1 (14 vs. 8 months; p = 0.018). The severity of LUTS could be determined by these parameters.Conclusion Based on the DVAISS, a prediction of the clinical course and approximate treatment duration is possible. Therefore, the DVAISS is useful to assess LUTS in children and is also a valuable tool in rating the severity of the disease. It is also a quite precise predictor of the time needed to resolve the symptoms.
Keywords: scoring system; children; incontinence; lower urinary tract symptoms; bladder bowel dysfunction